Host Migration and Size Do Not Influence the Prevalence of Most Chewing Lice (Phthiraptera: Amblycera and Ischnocera) on Shorebirds (Aves: Charadriiformes) across the World - Alexandra Ashley Grossi; Myung-Bok Lee; Chunpo Tian; Fasheng Zou; Chi-Yeung Choi; Daniel Roland Gustafsson (Diversity, 2023)
Patterns of prevalence in chewing lice (Phthiraptera) on wild birds are poorly known, as are the underlying factors that influence these patterns. Here, we analyze a data set consisting of published prevalence data of lice on shorebirds, as well as new prevalence data from shorebirds examined in Australia, Canada, China, Japan, and Sweden between 2007 and 2020. In total, prevalence data from 10 genera of lice from over 110 host species were included, including all major families of shorebirds. Using a generalized linear mixed model, we examine how the prevalence of lice of different genera varies between different sets of birds, focusing on two factors associated with migration (migration length and migration route). We found that host body size does not influence prevalence of lice in the Charadriiformes for any of the four most common and widely distributed louse genera (Actornithophilus, Austromenopon, Quadraceps, and Saemundssonia). Moreover, neither of the two migration variables showed any statistically significant correlations with prevalence, except for the genus Saemundssonia in which the prevalence of lice on short-distance migrants was significantly higher than on intermediate- and long-distance migrants. We also present 15 new records of chewing lice for China and 12 for Australia.